Equilibrium configurations of director in a planar nematic cell with one spatially modulated surface - Ledney, M.F.; Tarnavskyy, O.S.; Lesiuk, A.I.; Reshetnyak, V.Yu. (Condensed Matter Physics, 2016)
We study two-dimensional equilibrium configurations of nematic liquid crystal (NLC) director in a cell confined
between two parallel surfaces: a planar surface and a spatially modulated one. The relief of the modulated
surface is described by a smooth periodic sine-like function. The director easy axis orientation is homeotropic
at one of the bounding surfaces and is planar at the other one. Strong NLC anchoring with both surfaces is
assumed. We consider the case where disclination lines occur in the bulk of NLC strictly above local extrema of
the modulated surface. These disclination lines run along the crests and troughs of the relief waves. In the approximation of planar director deformations we obtain analytical expressions describing a director distribution
in the bulk of the cell. Equilibrium distances from disclination lines to the modulated surface are calculated and
their dependences on the cell thickness and the period and depth of the surface relief are studied. It is shown
that the distances from disclination lines to the modulated surface decrease as the depth of the relief increases. Дослiджено двовимiрнi рiвноважнi конфiгурацiї директора нематичного рiдкого кристалу (НРК) в комiрцi
обмеженiй двома паралельними поверхнями: планарною i просторово модульованою. Форма рельєфу
модульованої поверхнi описується гладкою перiодичною синусоподiбною функцiєю. Розглянуто випадок
наявностi дисклiнацiйних лiнiй в об’ємi НРК строго над локальними екстремумами модульованої поверхнi, що проходять вздовж гребенiв i западин хвиль рельєфу. Виникнення дисклiнацiйних лiнiй зумовлене
рiзним типом орiєнтацiї легкої осi директора на обмежуючих поверхнях комiрки (гомеотропна орiєнтацiя
на однiй з обмежуючих поверхонь i планарна на iншiй) та жорстким зчепленням НРК з поверхнями. В наближеннi плоских деформацiй директора отримано аналiтичнi вирази для розподiлу директора в об’ємi
комiрки. Розраховано рiвноважнi вiдстанi вiд дисклiнацiйних лiнiй до модульованої поверхнi та знайдено
їх залежнiсть вiд параметрiв комiрки (перiоду та глибини хвиль рельєфу), а також вiд товщини комiрки.
Показано, що вiдстанi вiд дисклiнацiйних лiнiй до модульованої поверхнi зменшуються зi зростанням
глибини рельєфу.